2018
DOI: 10.1097/md.0000000000011046
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prevalence of adrenal insufficiency in hemodynamically stable patients with cirrhosis

Abstract: It is well known that adrenal insufficiency is common in septic shock or hemodynamically unstable patients. But, there is as yet no sufficient clinically significant data about the exact prevalence or differences in the cause of cirrhosis with adrenal insufficiency. To investigate adrenal insufficiency prevalence in hemodynamically stable patients with cirrhosis and determine differences based on cirrhosis severity or etiology.From July 2011 to December 2012, 69 hemodynamically stable patients with cirrhosis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 26 publications
(42 reference statements)
3
41
0
Order By: Relevance
“…In addition, the characterization of RAI in non-critically ill patients with cirrhosis has been somewhat problematic as the optimal methodology for assessing RAI remains debated. [18][19][20] Traditional measurement of HPA axis function relies on the measurement of serum total cortisol levels in response to synacthen administration.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the characterization of RAI in non-critically ill patients with cirrhosis has been somewhat problematic as the optimal methodology for assessing RAI remains debated. [18][19][20] Traditional measurement of HPA axis function relies on the measurement of serum total cortisol levels in response to synacthen administration.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies were primarily conducted in cirrhotic patients. For instance, the study from Park et al revealed no association between serum cholesterol and AI in cirrhotic patients, while Spadaro et al stated that cirrhosis with low total cholesterol exhibited an association with AI [17,23]. In the general hospitalized patient, serum total cholesterol level is not associated with serum random cortisol and AI [14].…”
Section: Discussionmentioning
confidence: 98%
“…Cirrhosis has been reported to be associated with biochemical AI in multiple studies with a prevalence from 25 to 54% [15,16]. The association between biochemical AI and serum albumin and cholesterol has been studied [14,17,18]. However, combined biochemical factors together with clinical factors to predict biochemical AI in hospitalized patients with equivocal serum cortisol levels have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported an association between serum cholesterol and AI in cirrhotic patients. Spadaro et al stated that low total cholesterol exhibited an association with AI, while Park et al found no association between serum cholesterol and AI in cirrhotic patients [26,27]. As cholesterol is a precursor of glucocorticoid synthesis, AI may be present when serum cholesterol is lower than normal.…”
Section: Discussionmentioning
confidence: 99%